Uso de aparelho extrabucal de Thurow modificado para tratamento de má oclusão de classe II: relato de caso - Nunes Neto, Antônio Pergentino (2016)
Malocclusion is an oral disease which has been regarded as an important public health problem due to the high prevalence in the world population and the functional and aesthetic impacts that cause in their carriers. The Angle Class II malocclusion is among the most prevalent in individuals seeking orthodontic correction. However, there is no consensus among professionals regarding the correct time and best therapeutic approach for the treatment of this disorder. This study aims to present a case in which was used the Thurow modified appliance to treat a patient with Class II malocclusion, division 1. A girl of nine years and three months, attended in the Children's Integrated Clinic of the Federal of Ceara University, with upper anterior teeth protruded main complaint. At the clinical and cephalometric examination, it was observed that the patient had mesofacial pattern and jaw protruding beyond the convex facial profile. The aesthetic dental index confirmed high severity of malocclusion, with mandatory treatment needs. At the end of the active phase of treatment, the growth pattern remained virtually unchanged, with noticeable difference in the profile and inclination of the upper incisors. There was a decrease in the severity of malocclusion. The headgear apparatus showed effectiveness in the treatment of Class II, division 1 malocclusion during facial growth, with restriction of maxillary growth and retraction of the upper incisors.